ANALISIS PENGUKURAN KINERJA PERUSAHAAN PADA PT RAJAWALI NUSANTARA INDONESIA CABANG MAKASSAR DENGAN PENDEKATAN BALANCED SCORECARD - Amril Amril (AkMen JURNAL ILMIAH, 2016)
The research objective to be achieved is to determine the performance of PT Rajawali Nusantara Indonesia Makassar branch when measured Scorecard.Metode Balanced approach analyzes were used that method Balanced Scorecard through the four perspectives, namely financial perspective, customer perspective, internal business processes, as well as the perspective of learning and pertumbuhan.Analisis financial perspective on the Return on Investment, Total Asset Turn Over and Liquidity only decreased from 2012 to 2013. This decline is considered normal so that firms can still be said likuid.Inovasi by PT Rajawali Nusantara Indonesia Makassar Branch enough well, and in general, employees feel quite satisfied working and learning index with an increase in training programs by the company to its employees has been good enough yet still make changes to the level of employee satisfaction is achieved.